Good clinical and MRI outcome after arthroscopic autologous chondrocyte implantation for cartilage repair in the knee - Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2018)
PurposeTo analyze the clinical outcome and cartilage regeneration after all-arthroscopic Autologous Chondrocyte Implantation (ACI) using chondrospheres® (ACT3D) for the treatment of full-size articular cartilage lesions at the knee.MethodsThirty consecutive patients treated by all-arthroscopic ACI for full-size articular cartilage lesions in an otherwise healthy knee were enrolled. The defects were located on the femoral condyles (n = 18), in the trochlea (n = 7) and at the patella (n = 5). Follow-up consisted of a clinical evaluation with assessment of subjective scores. Patient satisfaction was evaluated on a visual analog scale (VAS). 3-Tesla MRI and T2 mapping of the operated and the contralateral healthy knees were included to control the quality of the regenerated cartilage. The MOCART score was assessed by three blinded independent radiologists.ResultsAt the mean follow-up of 3 years ± 10.2 months 26 of the 30 patients (86.6%) were subjectively highly satisfied with the surgical result and assured they would undergo the same procedure again. The mean Lysholm score increased to 77.7 ± 14.6, the mean subjective IKDC significantly to 84.2 ± 5.6 (p < 0.05) and all five subgroups of the KOOS improved significantly (p < 0.05). The subjective outcome was not influenced by the duration of symptoms, age, location, size of defects nor dose of spheroids. The modified MOCART score was a mean of 60 ± 21 (0-80) points. Twenty-four patients (82.7%) were rated higher than 60 points. T2 mapping documented similar cartilage quality of the area of the ACI and the same location at the contralateral knee. Three patients had a MOCART score of 0 with few or no cartilage regeneration on MRI and were considered as failure of the ACI.ConclusionIn this small cohort of 30 patients, minimal invasive all-arthroscopic ACT 3D using spheroids led to convincing clinical short-to-mid-term results with a significant increase in patients quality of life, satisfaction, reduction of pain, and improvement in knee function. The high morphologic integrity and quality of the ACI was reconfirmed by the Mocart Score and T2 mapping.Level of evidenceIV.